CORRELATION OF CAREGIVERS’ STRAIN WITH PATIENTS’ DISABILITY IN STROKE - Adan Sardar; Khurram Shahzad; Abdul Rehman Arshad; Khawar Shabbir; Syed Hassan Raza (Journal of Ayub Medical College Abbottabad, 2022)
Background: Stroke results in serious long-term disability in fifty percent of the survivors, making them dependent on others for activities of daily living. Our study aims to study the effect of this dependence on care-givers. Cross sectional study. Methods: It was a cross sectional study conducted at Combined Military Hospital Peshawar from September 2020 to November 2020. Self-administered questionnaires were used to interview 96 patients with stroke and their caregivers selected through convenience sampling technique. Barthel Index was used to measure disability among patients, whereas Modified Caregivers Strain Index (M-CSI) was used for the caregivers. An association between the two scores was analyzed through Pearson’s coefficient of correlation (r) and linear regression. Results: Mean ages of the patients and their caregivers were 66.13±11.32 and 36.32±13.71 years respectively. Median score of Barthel index was 1.00 (interquartile range 0.00- 9.75). Mean M-CSI score was 17.31±5.04. There was significant negative correlation between Barthel Index and M-CSI (R=0.542, p<0.001). No significant association was found between duration of stroke and history of recurrent stroke with Barthel Index (p=0.399 and p=0.527 respectively). Conclusion: Greater the dependence of patients for activities of daily living on their caregivers, higher is the level of strain among the latter. There is dire requirement of social support and rehabilitation centers to address the physical and mental needs of both the patients and their care providers.